PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN PT. FUMIRA SEMARANG) - Deni Wicaksono Nugroho; Ari Pradhanawati (Universitas Diponegoro, 2019)
This research was conducted with the aim of gaining an understanding of compensation and motivation for employee performance. This research was conducted at PT. Fumira Semarang. The research sample borrowed 72 respondents in the production department. This study consists of 17 indicators, 3 variables and 3 hypotheses. The analytical tool used is SPSS 19.0 for Windows with validity test, reliability test, test coefficient test, coefficient of determination, simple and multiple regression analysis, and significance test (t test and F test). The results of this study show a partial comparison (X1) positive and significant effect on employee performance (Y), based on the results of a simple linear regression test Y = 3.509 + 0.436 X1 with a t count of 15.602 greater than t table of 1.666 which shows Ho rejected and Ha accepted . Comparison coefficient of compensation to employee performance of 0.881 which means it has a strong and direct relationship between compensation and employee performance. The coefficient of compensation determination is 77.3%. The results of respondents' answers to compensation for compensation of employees of PT. Fumira is in the good category of 38.9%. While motivation (X2) has a positive and significant effect on employee performance (Y) with results Y = 2.929 + 0.551 X2, t arithmetic motivation of 14.895 is higher than t table of 1.666 which shows Ho is rejected and Ha is accepted. Motivation coefficient of 0.872 indicates a strong and direct relationship to employee performance with the coefficient of determination of motivation on employee performance of 75.7%. The results of respondents' answers to the motivation of PT. Fumira is in the good category of 55.6%. Variable compensation (X1) and motivation (X2) with positive and significant simultaneous effect on employee performance (Y) with the results Y = 2.226 + 0.250X1 + 0.282X2 with an F count of 147.777 is greater than the F table of 3.13 selected Ha accepted and Ho refused. The coefficient value of 0.914 shows a strong relationship between compensation and motivation on employee performance. Based on the results of the study, PT. Fumira Semarang is expected to provide appropriate and timely compensation to employees and increase the level of payments and bonuses as a form of company appreciation for its employees. Companies are expected to provide training and coaching more often for employees to create expertise and improve the skills of employees.